Analysis of Clean Water Availability in Batas Hamlet and Tol-tol Hamlet, Pringgondani Village, Sumberjambe District - Tatrisya Derka, Icha; Amiluddin, Afif; Faradella, Maulida; Katminto, Katminto; Hanurani, Devi (Fakultas Teknik, Universitas Brawijaya, 2026)
Flash floods in Pringgondani Village have caused significant damage to infrastructure, including disruptions to the clean water supply, thereby affecting environmental, economic, and social conditions. Limited access to safe water poses serious public health risks; therefore, mitigation efforts are essential to enhance the resilience of the water supply system. This study aims to project water demand over the next ten years and to determine the required reservoir storage capacity. A quantitative descriptive approach with community participation was employed, incorporating water demand projections based on population growth and rainfall analysis using a simple runoff method to estimate water availability. The results indicate that the projected water demand over the next ten years will reach 854,012.1 L/day for a population of 7,189 inhabitants. The analysis also shows that the required storage volume for Batas and Tol-tol hamlets is 9.96 m³, while the total reservoir capacity required for Pringgondani Village is approximately 79.75 m³. To ensure an adequate and reliable water supply, the required storage can be achieved by constructing three reservoirs, each measuring 3 m × 3 m × 3 m, providing a total storage capacity of 81 m³, which is sufficient to meet the projected demand. Currently, only two reservoirs with a total capacity of 54 m³ are available, which is insufficient for future demand. Therefore, one additional reservoir supported by a larger-capacity water source is recommended to improve system reliability, meet future demand, reduce the impacts of dry seasons, and provide backup capacity during emergencies such as flash floods.